Effect of Crude Palm Oil Protection on Fermentation Parameter and Rumen Microbial Activity of Male Local Lamb - Tiven, NC; Yusiati, LM; Rusman, Rusman; Santoso, U (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2012)
Abtstract. The experiment was conducted to determine the effect of protected crude palm oil (CPO) protection in the ration on in vivo fermentation parameters and microbial activity. Fifteenth local male lambs aged 9-12 months weighing 14-17 kg, were divided into 3 groups ration treatment. The first group received only the basal ration (R0), the 2nd group received the basal ration and 3% CPO (R1), while the 3rd group received the basal ration and 3% CPO protected with 2% formaldehyde (R2). The data were analyzed by completely random design with oneway pattern. The different of treatments were tested by Duncanâs New Multiple Range Test. The results showed that addition CPO protected with formaldehid (R2) in sheep ration increasing microbial protein in the rumen fluid.Keywords: fermentation parameters, rumen microbial activit. CPOÂ Abstrak. Penelitian ini dilakukan untuk mengetahui pengaruh proteksi kelapa sawit mentah (CPO) dalam ransum terhadap parameter fermentasi in-vivo dan aktivitas mikroba. Lima belas ekor domba lokal muda jantanumur 9-12 bulan dengan bobot 14-17 kg, dibagi menjadi tiga kelompok perlakuan ransum. Kelompok pertama hanya diberi ransum basal (R0), kelompok kedua diberi ransum basal dan 3% CPO (R1), kelompok ketiga diberi ransum basal dan 3% CPO terproteksi dengan 2% formaldehid (R2). Rancangan Acak Lengkap dan dan anova satu arah digunakan pada penelitian ini dengan uji lanjut jarak ganda Duncan. Hasil penelitian menunjukkan bahwa penambahan CPO terproteksi dengan formaldehida (R2) pada ransum domba meningkatkan protein mikroba dalam cairan rumen.Kata kunci: parameter fermentasi, aktivitas mikroba rumen, CPOÂ NC TivenÂ et al/Animal Production 14(3):141-146, September 2012